Hypertension associated with osteoporosis in female patients of the Seguro Social de Salud hospital, Trujillo - De La Cruz-Burgos, Jeanpierre (2022)
Objective: To determine if hypertension is associated with osteoporosis in female patients of Seguro Social de Salud (EsSalud) Hospital I in Trujillo.Materials and methods: An observational, analytical and cross-sectional study, which included 351 female patients treated in the Internal Medicine Unit of EsSalud Hospital I Florencia de Mora, Trujillo, from 2016 to 2019. According to the screening criteria, patients were divided into two groups—175 with hypertension and 176 without hypertension—to determine the number of patients with osteoporosis. The data was analyzed with Pearson’s chi-square test using IBM SPSS Statistics V26 to perform the statistical analysis and present the results in graphs and tables in Microsoft Excel Windows 10.Results: It was found that the prevalence of osteoporosis with hypertension accounted for 31.4 %, while that of osteoporosis without hypertension was 1.7 %. This shows that the prevalence of osteoporosis in women with hypertension is statistically significant (p < 0.001) with respect to women without hypertension. Regarding the analysis of the intervening variables, age (p < 0.001), cholesterol (p < 0.001) and coffee (p < 0.001) were statistically significant. Variables such as type 2 diabetes mellitus, sex, obesity, anemia, triglycerides and smoking were not statistically significant.Conclusions: Hypertension is associated with osteoporosis as well as with the intervening variables age, cholesterol and coffee, as they were statistically significant.